The Availability, Utilisation and Needs for Continuing Professional Development of Rural General Practitioner in the Western and Northern Cape - M.R. de Villiers (South African Family Practice)
Continuing professional development (CPD) is receiving increasing attention in South Africa. The introduction of recertification based on a system of obligatory CPD by the Health Professions Council of South Africa has precipitated a flurry of activity in the CPD arena, especially in terms of providing CPD. However, despite the fact that the assessment of learning needs has a positive influence on the outcome of CPD not much has been done in South Africa to assess the real, perceived and expressed educational needs of doctors.